Corporate Social Responsibility in Romanian Companies – between Perceptions and Reality - Ciprian Obrad; Dalia Petcu; Vasile Gherheş; Sorin Suciu (Amfiteatru Economic Journal, 2011)
Starting with the premise that corporate social responsibility is a major factor for lasting development in a global economic society, this article sets forth an analysis of the realities and tendencies within the Romanian CSR. The present article offers the analysis done after the research of the organization, coordination, and activity model for CSR in Romanian companies, and of the benefits these have as a consequence of socially responsible involvement within the communities they relate to. We focused on communication methods and the transparency degree within CSR activities of these companies, and we noticed the perceptions regarding the specifics of local CSR.
Keywords: M14; 330; corporate social responsibility; transparency; communication; social reporting